Metastasis from Intracranial Mesenchymal Chondrosarcoma: Report of a Rare Case - Dutta, Gautam; Singh, Daljit; Saran, Ravindra Kumar; Singh, Hukum; Srivastava, Arvind Kumar; Jagetia, Anita (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Chondrosarcoma is a rare malignant tumor originating from cartilaginous tissue with a tendency to localize in the epiphysis of long and pelvic bones. Only 7% of all chondrosarcomas originate in the craniocervical region. Metastasis from intracranial chondrosarcoma is extremely rare with only two previously reported cases. We report on a young patient with intracranial chondrosarcoma who presented with extracranial metastasis 2 years after surgical excision of the primary lesion. Gross total excision combined with radiotherapy so far has led to a favorable outcome.
Keywords: chondrosarcoma; intracranial; metastasis; extracranial